Complex-valued in-medium potential between heavy impurities in ultracold atoms - Akamatsu, Yukinao; Endo, Shimpei; Fujii, Keisuke; Hongo, Masaru (Physical review, 2024)
We formulate the induced potential in a finite-temperature cold-atomic medium between two heavy impurities, or polarons, which is shown to be complex valued in general. The imaginary part of the complex-valued potential describes a decoherence effect, and thus the resulting Schrödinger equation for the two polarons acquires a non-Hermitian term. We apply the developed formulation to two representative cases of polarons interacting with medium particles through the 𝑠-wave contact interaction: (i) the normal phase of single-component (i.e., spin-polarized) fermions using the fermionic field theory and (ii) a superfluid phase using the superfluid effective field theory, which is valid either for a Bose-Einstein condensate (BEC) of a single-component Bose gas or for the BEC-BCS crossover in two-component fermions at a low-energy regime. Computing the leading-order term, the imaginary part of the potential in both cases is found to show a universal 𝑟−2 behavior at long distance. We propose three experimental ways to observe the effects of the universal imaginary potential in cold atoms.